Discrete optimization - Aardal, K. (Karen); Nemhauser, George L.; Weismantel, R. (Handbooks in operations research and management science, 2005)
The chapters of this Handbook volume cover nine main topics that are representative of recent theoretical and algorithmic developments in the field. In addition to the nine papers that present the state of the art, there is an article on the early history of the field. The handbook will be a useful reference to experts in the field as well as students and others who want to learn about discrete optimization.